2023
DOI: 10.3390/cancers15082219
|View full text |Cite
|
Sign up to set email alerts
|

Minimally Invasive Anatomic Liver Resection for Hepatocellular Carcinoma Using the Extrahepatic Glissonian Approach: Surgical Techniques and Comparison of Outcomes with the Open Approach and between the Laparoscopic and Robotic Approaches

Abstract: Surgical techniques and outcomes of minimally invasive anatomic liver resection (AR) using the extrahepatic Glissonian approach for hepatocellular carcinoma (HCC) are undefined. In 327 HCC cases undergoing 185 open (OAR) and 142 minimally invasive (MIAR; 102 laparoscopic and 40 robotic) ARs, perioperative and long-term outcomes were compared between the approaches, using propensity score matching. After matching (91:91), compared to OAR, MIAR was significantly associated with longer operative time (643 vs. 579… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 34 publications
0
4
0
Order By: Relevance
“…15 When patients have good liver function, anatomical liver resection is the preferred surgical approach for early-to-intermediate stage liver cancer, as it effectively reduces intrahepatic recurrence by removing the portal vein system and improves overall survival. [15][16][17][18][19] However, the surgical margin is also a key factor affecting long-term prognosis in patients undergoing anatomical liver resection. 20,21 Zhang et al study showed that among MVI-positive HCC patients undergoing anatomical liver resection, those with a surgical margin less than 1 cm had poorer 1-, 3-, and 5-year recurrence-free survival rates and overall survival rates compared to patients with a surgical margin greater than 1 cm.…”
Section: Discussionmentioning
confidence: 99%
“…15 When patients have good liver function, anatomical liver resection is the preferred surgical approach for early-to-intermediate stage liver cancer, as it effectively reduces intrahepatic recurrence by removing the portal vein system and improves overall survival. [15][16][17][18][19] However, the surgical margin is also a key factor affecting long-term prognosis in patients undergoing anatomical liver resection. 20,21 Zhang et al study showed that among MVI-positive HCC patients undergoing anatomical liver resection, those with a surgical margin less than 1 cm had poorer 1-, 3-, and 5-year recurrence-free survival rates and overall survival rates compared to patients with a surgical margin greater than 1 cm.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, the oncological outcomes of MILS may be further optimized by conducting more frequent anatomic liver resections when feasible. This is substantiated by recent randomized clinical trials [ 48 , 56 ] and the escalating utilization of innovative techniques, such as indocyanine green fluorescence navigation. This navigational approach has exhibited promise in enhancing the achievement of liver resections with tumor-free margins, as evidenced by a published study indicating increased disease-free survival after MILS with indocyanine green fluorescence navigation compared to MILS without it [ 57 ].…”
Section: Does Mils Improve Post-resection Outcomes?mentioning
confidence: 94%
“…Nevertheless, the discussion surrounding the influence of MILS on long-term outcomes post HCC resection is characterized by nuanced debates, primarily resulting from the dearth of randomized trials and conflicting evidence among available studies. While a majority of studies report comparable outcomes between MILS and the open technique, emerging evidence suggests that the benefits of MILS may extend beyond the short term to positively impact long-term oncological endpoints [ 48 , 49 ]. A recent large cohort study with propensity score matching from Japan and Korea showed that laparoscopic liver resection had a better mid- and long-term disease-free survival than open hepatectomies [ 50 ].…”
Section: Does Mils Improve Post-resection Outcomes?mentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, the optimal approaches or techniques to expose the intersegmental hepatic veins are still undefined. We have previously reported our standardized techniques of MIAS using the extrahepatic Glissonean approach (EGA) and hepatic veinroot at first cranial-to-caudal parenchymal dissection, based on the anatomical background of Laennec's capsule of the liver [9,[11][12][13][14]. A few studies from other authors reported their techniques and favorable surgical outcomes of laparoscopic AS using EGA [15,16].…”
Section: Introductionmentioning
confidence: 99%